Effectiveness of Waqf Management in the Framework of Creating the Welfare of the People - Mahin Musyafa; Aryani Witasari (UNISSULA Semarang, 2021)
The objectives of this study are: 1) To determine and analyze the effectiveness of waqf management according to Law Number 41 of 2004 for the welfare of the people, 2) To determine the inhibiting factors in waqf management, 3) To find solutions to overcome the inhibiting factors in waqf management.The approach method used in this research is the sociological juridical method. The specification of this research is a research with a descriptive analytical description of the specification. Sources of research data in the form of primary and secondary data. Collecting data using literature study as the main data and interviews as supporting data. Methods of data analysis using qualitative analysis methods, namely, data reduction, presenting data and concluding.The results of the study stated thatThe effectiveness of waqf management for the welfare of the people is based on Nazhir on duty. In this case, the management of Waqf according to Law No. 41 of 2004 in order to realize the welfare of the people has not been effective because of the lack of knowledge about the administration of waqf assets. The inhibiting factor faced in the management of waqf in order to realize the welfare of the people is that nâzhir is not optimal in managing waqf, the government is not socializing Law no. 41 of 2014 and PP No. 42 of 2006, and low public awareness to carry out waqf management activities. Hence the solution waqf management in realizing the welfare of the people, namely synergies with related agencies in the form of government efforts to regulate regulations related to these problems which are carried out by optimally empowering religious institutions.